Incidence of Smartphones in the development of brain plasticity in children from 0 to 6 years old, in a context of high vulnerability - Manuel Salum Tome , Jose; Angel Ponce Lopez, Miguel (Seven Editora, 2023)
The research project presented below essentially aims at a systematic review regarding the use of Smartphones in the development of brain plasticity in children aged between 0 and 6 years. This review will be composed of three large categories of content: Intellectual, Attitudinal and Behavioral, each of which is made up of a certain number of Skills, which will be expressed according to the different systematic reviews, including gray literature, which will provide the basis and theoretical and practical foundations that would allow the deduction of new research. DOI: 10.56238/pacfdnsv1-102